Pengaruh Terapi Art (Mengambar) Terhadap Peningkatan Harga Diri Anak/Remaja Di Puskesmas Bone Bolango - Hinur, Febriani; I. Biahimo, Nur Uyuun (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Efforts can be made to improve activities in patients who experience low self-esteem by inviting patients to do positive affirmations, providing logotherapy and also drawing therapy. Methods: The research used in this study was pre-experimental with a one-group pre-post test design approach, the population was all child or adolescent patients who experienced low self-esteem in the Bone Bolango Health Centre area, namely 15 people, so the number of samples in this study was the same as the population of 15 respondents. Results: Based on the results of statistical tests using the Wilcoxon test, a significant value or PValue of 0.000 was obtained, which means 0.000 <0.05 so it can be concluded that Ha is accepted, which means that there is an effect of art therapy (drawing) on increasing self-esteem in children / adolescents at Puskesmas Bone Bolango. Conclusion: It is hoped that it can add information for health workers so that it is hoped that health workers can apply art therapy (drawing) in increasing the self-esteem of patients who experience low self-esteem.